Complexity in evolved regulatory variation for alcohol dehydrogenase genes in Hawaiian Drosophila. - Fang, X.M.; Wu, C.Y.; Brennan, M.D. (Journal of Molecular Evolution, 1991)
The alcohol dehydrogenase gene (Adh gene) of Drosophila affinidisjuncta is expressed at a higher level in the larval midgut and Malpighian tubules than the homologous gene from Drosophila hawaiiensis. This study analyzed the cis-acting sequences responsible for these regulatory differences in larval tissues of Drosophila melanogaster transformants. A series of 10 chimeric and deleted Adh genes was introduced into the germ line of D. melanogaster, and tissue-specific expression levels were quantified by gel electrophoresis of tissue extracts. Sequences in the upstream region of the two genes had the strongest influence on enzyme production in the midgut and Malpighian tubules. Other sequence elements also showed effects, some of which were tissue specific. Most gene fragments displayed context-dependent effects, thus supporting the proposed model of polygenic regulation of Adh gene expression.